KEWENANGAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM MENANGANI SENGKETA WANPRESTASI KASUS JUAL BELI UNIT RUMAH DI NEW ACACIA GARDEN LIPPO CIKARANG - Sela Nopela Milinum, (2022)
The Consumer Dispute Settlement Agency (BPSK) is a non-litigation consumer dispute resolution agency. In practice, few BPSK decisions were canceled by the District Courts and even reached the Supreme Court because the disputes handled by BPSK were not consumer disputes. This also adds to the length of the case resolution process. The research method used is normative juridical, referring to secondary data sources or library materials with a statutory and case approach. The analysis technique of this research is descriptive qualitative. The results show that BPSK in a quo case is not authorized to resolve default disputes because it is not within the scope of its duties and authorities as regulated in Article 52 UUPK jo. Article 3 Kepmenperindag Number 350/MPP/Kep/12/2001. The Cikarang District Court in its Decision Number 276/Pdt.Sus-BPSK/2019/PN.Ckr granted the objection filed by PT. Lippo Cikarang Tbk and cancel BPSK Decision No. 21/BPSK-BKS/2019 which in this case was confirmed by Supreme Court Decision Number 601K/PDT.SUS-BPSK/2020 by rejecting the appeal filed by Sri Ratih Sekar Ayu Ningsih. The canceled BPSK decision does not have binding legal force anymore so it has legal consequences for Sri Ratih Sekar Ayu Ningsih where she must be responsible for her default as stipulated in the applicable provisions. BPSK is expected to pay more attention to cases that will be handled according to their authority so that the parties can obtain effective settlement steps. The government is to revise the UUPK, especially related to regulations that are still overlapping, namely regarding the submission of objections to the BPSK Decision to the District Court. Consumers and business actors must first understand well and fulfill their obligations according to the agreement in good faith before agreeing.